A 3-D U-shaped meander-line slow-wave structure for traveling-wave-tube applications - Chua, Ciersiang (2013)
A novel 3-D U-shaped meander-line (ML) slow-wave structure (SWS) is proposed for traveling-wave-tube applications. This 3-D structure has the potential to have a better performance than the corresponding 2-D ML SWSs proposed in the literature. Simulation results at S-band obtained using CST Microwave Studio are presented to compare the phase velocity, interaction impedance, and circuit attenuation of the proposed structure with those of a recently reported symmetric double V-shaped microstrip ML SWS, showing advantages with respect to circuit attenuation, bandwidth, and feed design. Particle-in-cell simulations are also carried out for the proposed structure for a cylindrical electron beam using CST Particle Studio. The saturated gain and electronic efficiency of the 3-D U-shaped ML SWS is significantly higher than that of the symmetric double V-shaped ML SWS. The proposed structure has been designed and fabricated with a microstrip-line feed at S-band. The measured return loss, phase velocity, and circuit attenuation match well with the simulation results. By using microfabrication techniques, the proposed SWS has the potential to operate at millimeter-wave and higher frequencies.